Impact of Faba Bean (Vicia faba L.) Diet and Subsequent Withdrawal on GIFT Tilapia (Oreochromis niloticus) Muscle Quality - Guanling Xu; Wei Xing; Tieliang Li; Shibo Wei; Ying Zhang; Tingting Song; Huanhuan Yu; Lin Luo (Fishes)
To systematically evaluate FB’s effects on tilapia muscle quality, two distinct experimental phases are designed, the crispy texture development phase (0–16 weeks) and the crispy texture retention phase (17–24 weeks), which can determine the minimum faba bean (FB) feeding duration required to achieve optimal textural modification and can assess the persistence of improved textural properties following FB withdrawal, respectively. The results demonstrated that a 60% FB inclusion diet administered for 16 weeks did not adversely affect tilapia growth performance. Significant improvements in textural parameters, including hardness, springiness, chewiness, and shear force, were observed in FB-fed tilapia as early as 8 weeks, with these enhancements being maintained throughout the 16-week feeding period. These superior textural characteristics persisted during the subsequent retention phase following FB withdrawal. Microstructural analysis revealed that the 60% FB diet significantly enhanced muscle-fiber density while reducing fiber diameter in tilapia during the 8–16 week feeding period. These microstructural modifications persisted throughout the texture retention phase, maintaining significant differences compared to the control group. Serological analysis demonstrated the FB group elevated Superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) levels at 4 weeks, though these differences normalized thereafter. qRT-PCR showed the 60% FB clearly increased the expression of mstn at 8 weeks, while col1a-2 and myog expressions also obviously improved at 12 weeks. In summary, dietary 60% FB improved tilapia muscle crispiness by altering texture and microstructure via gene-expression regulation. The minimum duration was 8 weeks to achieve crispiness in tilapia by the 60% FB diet without adverse effects on growth, immunity, and hepatopancreas function. Furthermore, the crispy texture of tilapia fillets was maintained for at least 2 months following withdrawal of the 60% FB diet after 16 weeks of continuous feeding.